2005
DOI: 10.1007/s00484-005-0277-z
|View full text |Cite
|
Sign up to set email alerts
|

Meteorology and the physical activity of the elderly: the Nakanojo Study

Abstract: Seasonal changes in ambient temperature and day length are thought to modify habitual physical activity. However, relationships between such environmental factors and the daily physical activity of older populations remain unclear. The present study thus examined associations between meteorological variables and the number of steps taken per day by elderly Japanese. Continuous pedometer counts over a 450-day period were collected from 41 healthy subjects (age 71+/-4 years), none of whom engaged in any specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
149
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(174 citation statements)
references
References 25 publications
19
149
6
Order By: Relevance
“…As temperature increased by 1°C, older men increased their total PA by 12 ct•min -1 , spent 2 min more in MVPA, and took 307 more steps per day. The results for older men confirm data from previous studies that used self-reporting and objective measures 11,23,25 and that found a curvilinear relationship between the number of steps taken and temperature in older adults. One of those studies showed that PA during the summer peaked at temperatures of 20°C and declined as temperatures continue to rise beyond this value, until it reached 30°C.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…As temperature increased by 1°C, older men increased their total PA by 12 ct•min -1 , spent 2 min more in MVPA, and took 307 more steps per day. The results for older men confirm data from previous studies that used self-reporting and objective measures 11,23,25 and that found a curvilinear relationship between the number of steps taken and temperature in older adults. One of those studies showed that PA during the summer peaked at temperatures of 20°C and declined as temperatures continue to rise beyond this value, until it reached 30°C.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies involving elderly adults based on pedometers found similar correlations between weather variables and PA 23 .…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In previous studies, weather conditions such as heavy rain, hot temperatures, very cold temperatures or icy conditions have been reported as barriers by older people (Tu et al 2004). It has also been shown that the length of the day, together with temperature can influence physical activity (Sumukadas et al 2009, Togo et al 2005; this combination is likely also to apply in Finland, where days are short in winter and darkness was reported to be a barrier by many of the present participants. However, we found no correlation between the time of the year when the interview was conducted and unmet physical activity need.…”
Section: Methodological Considerationsmentioning
confidence: 69%
“…Several studies among adults report that poor weather is perceived as a barrier to physical activity [6][7][8][9][10] and that daily physical activity levels decrease as ambient temperature drops and also decrease with rain and snowfall. 11,12 People with functional limitations reported that curb ramps become particularly hazardous in winter. [13][14][15] A prime indicator of the accessibility of an architectural environment is the degree to which the environment enables the performance of relevant activities by its users.…”
Section: Introductionmentioning
confidence: 99%